Implementation Of The Numbered Head Together Model To Improve Student Activeness And Learning Outcomes - Gultom, Anastasya Tifani Mutiara; Zainal, Andri; Thohiri, Roza; Sibarani, Choms Gary Ganda Tua (Jurnal Ilmu Pendidikan dan Sosial, 2025)
The main problem in this study is the low level of student activity and learning outcomes. The purpose of this study is to determine the extent to which the increase in student activity and learning outcomes of class XI at SMKN 6 Medan through the application of the Numbered Heads Together (NHT) model.This study uses a classroom action research (CAR) method which is carried out in two cycles. The subjects of this study were 35 class XI AKL 2 students, while the object of the study was the application of the Numbered Heads Together learning model. Data collection techniques used in this study include observation and test administration. Based on the cycle I observation sheet, there were 13 students (37.14%) included in the active and very active categories, but had not achieved the success indicators. In cycle II, the number of students in the category increased to 33 people (94.28%) and had met the success criteria of ≥75%. The results of the learning test data analysis showed that the average pre-test score was 77.02 with 12 students (34.28%) completing it. In the post-test of cycle I, the average score increased to 85.31 with 30 students (85.71%) completing it. In the post-test of cycle II, the average score increased to 89.34 with 35 students (100%) achieving completion by meeting the success indicator ≥85%. Based on this analysis, it can be concluded that the application of the Numbered Heads Together learning model is effective in increasing the activeness and learning outcomes of class XI students at SMKN 6 Medan.